The role of independent fiscal policy institutions - Lars Kunze (Center for Economic Studies and ifo Institute (CESifo), 2011)
The paper analyses how independent fiscal watchdogs (fiscal policy councils) can strengthen the incentives for fiscal discipline. By increasing fiscal transparency they can raise the awareness of the long-run costs of current deficits and increase the reputational costs for governments of violating their fiscal rules. Councils that make also normative judgements, where fiscal policy is evaluated against the government's own pre-set objectives, are likely to be more influential than councils that do only positive analysis. To fulfil their role adequately, fiscal watchdogs should be granted independence in much the same way as central banks.
Keywords: H60; 330; fiscal institutions; deficit bias; fiscal transparency; Finanzpolitik; Wirtschaftspolitische Beratung; Öffentliche Finanzkontrolle; Autonomie; Haushaltskonsolidierung; Europa